KEPEMIMPINAN PEREMPUAN (Kajian Strategis Kepemimpinan Berbasis Gender) - Suyatno, Suyatno (IAIN Pekalongan, 2014)
Abstract : Terms of women's emancipation or gender equality is often touted in almost all corners of the world, able to open a general idea to rethink creature named women to become leaders, even heads of state. The discussion will be more interesting when the position of women in the social facts are also removed. It is of course behind the reconstruction of the position of women in the historical and political arena. Both studies and evidence from the Quran, the Hadith, and the explanation of the experts in the field, shows that women do not experience gender barriers to explore her potential and release energy to become a leader in the community when the community around it has not considered taboo and acknowledged benefits. In addition, the permissibility of being a leader must also be supported by personal qualities include: ability, capacity, faculty, and skills. Abstrak : Ketentuan emansipasi perempuan atau kesetaraan gender sering disebut-sebut hampir di seluruh penjuru dunia, mampu membuka ide umum untuk memikirkan kembali makhluk bernama perempuan untuk menjadi pemimpin, bahkan kepala negara. Pembahasan akan lebih menarik bila posisi perempuan dalam fakta-fakta sosial juga dihapus. Hal ini tentu saja di balik rekonstruksi posisi perempuan di arena sejarah dan politik. Kedua studi dan bukti dari Al-Qur'an, Hadits, dan penjelasan dari para ahli di lapangan, menunjukkan bahwa wanita tidak mengalami hambatan gender untuk menggali potensi dan melepaskan energi untuk menjadi pemimpin di masyarakat ketika masyarakat di sekitarnya belum tabu dipertimbangkan dan manfaat diakui. Selain itu, kebolehan menjadi seorang pemimpin juga harus didukung oleh kualitas pribadi meliputi: kemampuan, kapasitas, fakultas, dan keterampilan